Louteria cerámicos helenísticos en Pompeya y Risan (Montenegro) - Heras Mora, F. Javier; Principal, Jordi (Rei Cretariae Romanae Fautorum Acta, 2022)
We present some fragments of large and flat ceramic vessels (platters), called louteria, appeared in the excavations of Pompeii and Risan. Both are two port cities of Greek roots, whose origins we have had the opportunity to investigate, within two international teams. We compare both groups of pieces, in particular their morphology and decoration, in order to approach to the study of the workshops and areas of influence, but especially of the maritime distribution of this type throughout the northern area of the central Mediterranean basin, probably shared, in part, with the amphora trade.